Sufi Orders as a Political Force: The History of Sufi Involvement in Politics and the Role of Sufi Orders - R, Rian; Darmis, Rahmi; Harun, Hamza (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This article examines the dynamics of the relationship between tariqa (Sufi orders) and politics in Islamic history. Tariqa have not only functioned as spiritual communities but have also acted as significant socio-political forces. By tracing the involvement of tariqa from the classical period, through the medieval and colonial eras, to the modern context, this article aims to demonstrate that tariqa possess a dual role: as religious institutions and as agents of socio-political change. The method employed is library research with a historical–sociological approach. The article concludes that tariqa have played an important role in shaping collective identity, political resistance, and social mediation within Muslim societies.